Analysis of Cas1-2 and Cas3 CRISPR immunity proteins in E. coli cell physiology - Reeves, Ryan Peter (2019)
CRISPR-Cas is an adaptive immune system which provides protection from invasive mobile genetic elements in prokaryotes. CRISPR-Cas immunity starts with acquisition: this involves the capture of DNA fragments called ‘prespacers’, which are then processed to become ‘protospacers’ and integrated into the host’s chromosome as ‘spacers’. Acquisition is catalysed by the Cas1-2 complex along with host factors. Although the spacer integration mechanism is well understood, the prespacer capture process remains cryptic. In the E. coli CRISPR I-E system, the products of replication fork collisions have been linked to prespacer capture by Cas1-2. By increasing the frequency of replication-fork collisions using an E. coli strain with an additional ectopic origin of replication, I show that the level of spacer acquisition increases in vivo compared to wild-type; providing evidence that RecBCD-helicase processed fragments from stalled DNA replication forks are captured as prespacers by Cas1-2. Furthermore, I demonstrate that spacer acquisition increases in E. coli under nutritional stress. I also show that N-terminal tags on Cas1 have a detrimental effect on acquisition in vivo, despite successful spacer integration activity in vitro; as well as investigating the role of Cas3 in a cell stress response; and initiating genetic work into the unusual CRISPR-Cas system of Marinitoga piezophila.